Investigation of surface roughness of Al7075 material coated with micro-arc oxidation method - Özcan, M. E.; Özler, L.; Parlak, Nihat (Taylor and Francis Ltd., 2015)
Micro-arc oxidation (MAO) is the process of coating with hard, abrasion- and corrosion- resistant surface by immersing the substrate in an electrolytic liquid by the effect of electrochemical reaction through the plasma discharge. In this study, two-step coating is applied on aluminium material (AA7075) by MAO method. In the first step, the samples are coated with aluminium oxide in the solution of potassium hydroxide, sodium aluminate and sodium phosphate. In the second step, coating is performed by adding 0.8 g/l Ti particles into the same solution. For both solutions, the frequency, voltage and coating time varied as 100–350 Hz, 450–550 V, 10–30 min, respectively. After the coating process, surface roughness measurements are carried out for analysing the effect of experimental parameters (voltage, frequency and coating time) and Ti addition. The surface roughness indices are averaged by measuring on three different areas of the coated samples. Also SEM observation and EDX analysis of the samples coated in titanium additive and non-additive solutions are carried out. As a result of this review, it has been observed that surface roughness increases with increasing voltage, frequency and coating time and the maximum increasing occurs with the voltage parameters. According to SEM observations, the sample coated on 450 V is smoother than the samples coated on 500 and 550 V. However, local bumps occurred on the samples by increasing coating voltage and frequency. In addition, the coating morphology is affected by the addition of Ti particles. Ti-added coatings are rougher than non-additive samples. © 2015, © 2015 Taylor & Francis.
Keywords: AA7075 aluminium; Al 2 O 3; coating; Micro-arc oxidation; surface roughness